Millet Bran: Unveiling Its Potential Health Benefits - Nimisha Vashishth; Neeleh Kumar Maurya (International Journal of Nutritions, 2024)
Millet bran, derived from various millet grains, has emerged as a potent nutritional source, rich in fiber, vitamins, minerals, antioxidants, and omega-3 and omega-6 fatty acids. Its rising popularity is driven by its gluten-free nature, nutrient density, and sustainability. This review aims to explore the potential health benefits of millet bran, focusing on its digestive health, blood sugar control, heart health, antioxidant properties, and fatty acid composition. The Millet brand offers a diverse nutritional profile, including macronutrients like carbohydrates, proteins, and fats and micronutrients such as iron, magnesium, and zinc. Millet bran demonstrates superior nutrient density compared to other grains and contains unique bioactive compounds like phenolic acids and flavonoids. Its vitamins, particularly B-complex and E, contribute to energy metabolism, immune function, and cellular protection. Millet bran's mineral richness supports bone health, immunity, and metabolism, addressing micronutrient deficiencies and promoting overall health. Furthermore, its antioxidants protect against cellular damage and inflammation, while its omega-3 and omega-6 fatty acids benefit cardiovascular and cognitive health. Integrating millet bran into balanced diets offers potential solutions for digestive health, blood sugar management, and heart health. Future research directions include clinical trials to assess its efficacy in managing specific health conditions and long-term studies to evaluate its impact on chronic disease risk and overall well-being. Understanding the mechanisms and interactions of millet bran components will enhance its utilization as a functional food and contribute to food security and sustainability efforts.
Keywords: Millet Bran; Omega 3 & 6; Paper health benefits; Vitamin Minerals; antioxidants